A Modified Scaled Spectral-Conjugate Gradient-Based Algorithm for Solving Monotone Operator Equations - Auwal Bala Abubakar; Kanikar Muangchoo; Abdulkarim Hassan Ibrahim; Sunday Emmanuel Fadugba; Kazeem Olalekan Aremu; Lateef Olakunle Jolaoso (Journal of Mathematics)
This paper proposes a modified scaled spectral-conjugate-based algorithm for finding solutions to monotone operator equations. The algorithm is a modification of the work of Li and Zheng in the sense that the uniformly monotone assumption on the operator is relaxed to just monotone. Furthermore, unlike the work of Li and Zheng, the search directions of the proposed algorithm are shown to be descent and bounded independent of the monotonicity assumption. Moreover, the global convergence is established under some appropriate assumptions. Finally, numerical examples on some test problems are provided to show the efficiency of the proposed algorithm compared to that of Li and Zheng.